Black servants and Captain's slaves: James Cook and the death of George Rupee. Issue 12 (21st September 2020) - Parsons, Harriet
Abstract: Captain James Cook's first voyage of Pacific exploration on the Endeavour, from 1768 to 1771, with the naturalist Joseph Banks, was one of the 18th century's most ambitious scientific ventures. Two of Banks' servants, Thomas Richmond and George Dorlton, were black men, and close reading of the records of their deaths in January 1769, suggests that one of them, Dorlton, was the Captain's slave, George 'Rupee'. The Admiralty had banned slavery on Royal Navy ships and Rupee's accidental death had unforeseen consequences for the expedition. Cook's role as captain required him to investigate, and potentially dole out punishment if a member of the crew was culpable. However, his personal interest in the judgement as Rupee's master, compromised his impartiality. Networks of personal loyalty were integral to the social architecture of command in the Georgian Navy, and Rupee's death threatened to upset this fragile equilibrium. In the following days, half truths burgeoned into lies and deception in the Endeavour ' s reporting systems. The escalating 'bad language' put the crew's confidence in Cook's command in jeopardy, until the Master, Robert Molyneux, took decisive action to stop its spread.